EVALUATION OF OXIDATIVE STRESS INDICES AND ANTIOXIDANT LEVELS IN PRE AND POST HEMODIALYSIS PATIENTS - G.RAJ; IVVALA ANAND SHAKER (International Journal of Pharma and Bio Sciences, 2013)
The present study was undertaken to evaluate the effect of oxidative stress in chronic renal failure patients before and after hemodialysis and compared to healthy control individuals. The study comprised of 30 hemodialysis patients compared with 30 healthy controls. The object of the present study was to investigate the possible free radical mediated tissue damage in CRF before and after dialysis, by measuring Malondialdehyde (MDA) which is marker of oxidative stress and L-carnitine for lipid peroxidation. MDA levels were found to be significantly increased in pre dialysis CRF patients as compared to the controls (P< 0.001) and the levels further increased in post dialysis CRF patients as compared to that in pre dialysis CRF patients (P <0.001). Antioxidant enzymes such as superoxide dismutase, catalase, reduced glutathione, glutathione peroxidase and the levels of antioxidants like Vitamin A, Vitamin E and Vitamin C along with L-carnitine were significantly decreased in pre dialysis patients as compared to the controls (P<0.001) and the values further significantly decreased in post dialysis patients as compared to the pre dialysis CRF patients (P<0.001). The result of study have shown there is considerable oxidative stress in patients with CRF, which is further exacerbated by hemodialysis, as evidenced by increased lipid peroxidation and low levels of antioxidant and L-carnitine.